(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Proverbs are popularly defined as short expressions of popular wisdom. Efforts to improve on the popular definition have not led to a more precise definition. The wisdom is in the form of a general observation about the world or a bit of advice, sometimes more nearly an attitude toward a situation. Irrespective of what field or profession one works in, the use of English is very important these days. Communication using English has become pertinent for all professionals in every formal sector. This is why we need to ensure that our command over the language is clear. Apart from ensuring that our grammar is perfect, we must also focus on using tools to enrich our communication. For example, we can use proverbs to explain ideas better.